חטאת as interpolative gloss: a solution to Gen 4,7 - Crouch, C.L. (De Gruyter, 2011)
This note suggests that Gen 4,7 can be rendered comprehensible by the removal of the term ht't, understanding its appearance as an interpolative gloss, and the interpretation of the remaining rbts as the subject of a nominal clause. This eliminates the lack of agreement between the feminine singular ht't and the three masculine singulars which follow, and it allows an interpretation of the verse which sees Cain being offered the option of reversing the decision made by Eve when she ate from the tree of the knowledge of good and evil.